Obesity associated reproductive and sexual syndrome (OARS) - a promising term or premature diagnosis? - Muhammad Hassan (Journal of the Pakistan Medical Association, 2026)
Madam, The article ’Obesity Associated Reproductive and Sexual Syndrome (OARS) in Men’, which attempts to create a new clinical syndrome to integrate obesity-triggered reproductive and sexual issues in men1. The approach to highlighting this poorly researched field deserves credit, although multiple scientific and methodological constraints need attention. The medical concept of OARS, which combines hypogonadism with sexual dysfunction and spermatogenesis impairment, shows alignmentwith observed clinical cases. OARS has never been studied as an integrated syndrome even though the authors create formal diagnosis standards using this untested framework according to the published report1. The lack of original cohort analysis and insufficient epidemiological evidence creates doubts about syndromic validity and possible medicalising of conditions independently of the proposed syndrome. The proposed criteria demand evidence of two out of three separate findings when diagnosing male sexual dysfunction or low testosterone values along with sperm abnormalities. Studies indicate the proposed criteria which include male sexual dysfunction as well as low testosterone levels and sperm abnormalities fail to demonstrate appropriate specificity levels. These alarm signs fail to show exclusivity with obesity, while they might stem from lifestyle or pharmacological or psychological elements independent of adiposity levels3. This broad diagnostic criterion results in false attribution of obesity in communities battling stress-induced mental health problems plus obesity presentations4. The article describes how obesity disrupts hypothalamic-pituitary-gonadal axis functions through leptin resistance and abnormal kisspeptin signalling, according to the article.1 Medical research supports these endocrine pathways, but they happen in various chronic diseases apart from obesity-related conditions5. The South Asian socio-cultural context would benefit significantly from including contributory lifestyle and epigenetic and sociocultural variables missing from the article. The absence of local clinical information raises significant concerns. The authors who belong to South Asian origins fail to present any demographic research data that would demonstrate local patient outcomes or prevalence statistics. The article depends on secondary studies, yet most cited research originates from countries with high incomes whose healthcare availability varies significantly from that of the Indian subcontinent. The treatment recommendations in this section involve endorsing both testosterone replacement therapy with aromatase inhibitors1. Although these prescriptions match some clinical protocols, they lack vital warning regarding pregnancy risks and cardiovascular risks and misuse possibilities in young patients who wish to maintain fertility potential2. The OARS represents an inventive medical approach to highlight an essential clinical matter.